Structural phase transition in two-dimensional tetramer-cuprate Na5RbCu4(AsO4)4Cl2 - Gnezdilov, V.; Queen, W.; Mo, X.; Pashchenko, M.; Gnatchenko, S.; Zvyagin, S.; Lemmens, P.; Pashkevich, Yu.; Bedarev, V.; Hwu, S.-J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Using Raman scattering and optical birefringence we have investigated a low-temperature phase transition in single crystal of the two-dimensional Na5RbCu4(AsO4)4Cl2. Phonon anomalies point to a first order nature of the transition. The observed transition is most probably related to a order-disorder transition of the Rb ion positions along the z axis within the ionic framework of mixed alkali metal chloride lattices.